Экспериментальные геоэлектрические исследования на Шебелинском газоконденсатном месторождении - Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н. (Видавничий дім "Академперіодика" НАН України, 2009)
Експериментальнi геоелектричнi дослiдження наШебелинському газоконденсатному родовищi (ГКР) виконанi у лютому 2008 р. з використанням експрес-технологiї “прямих” пошукiв та розвiдки скупчень вуглеводнiв (ВВ), яка мiстить методи становлення короткоiмпульсного поля (СКIП) вертикального електрорезонансного зондування (ВЕРЗ) i флюксометричну зйомку. Згiдно з результатами проведених дослiджень, закартована аномалiя типу поклад (АТП) добре збiгається з контуром Шебелинської структури; зйомкою СКIП у межах Захiдно-Шебелинської площi не пiдтверджуються заявленi для неї прогнознi ресурси ВВ; три АТП виявленi зйомкою СКIП поблизу Шебелинської структури; масивно-пластовий поклад ВВ фiксується дiаграмою зондування в межах Шебелинського ГКР; iнтервал iнтенсивного нафтогазонасичення встановлено за межами Шебелинської структури на глибинах 5500–6600 м; технологiю СКIП – ВЕРЗ можна використовувати для оперативної оцiнки перспектив нафтогазоносностi глибинних (понад 6000 м) горизонтiв осадочного чохла. The results of experimental geoelectric investigations on the Shebelinka gas-condensate deposit (Dnieper-Donets depression) in February of 2008 are given. The innovative express-technology of “direct” searching and prospecting for hydrocarbon reservoirs has been used. The technology includes the method of formation of short-pulsed electromagnetic field (FSPEF), flux-meter survey and method of vertical electric-resonance sounding (VERS). Integrated application of these methods allows to find and map on the area the “deposit” type anomalies (DTA), and to define the total thi-ckness and bedding depths. The results show following: a) the mapped deposit-type anomaly (DTA) well coincides with the Shebelinka structure contour; b) the FSPEF survey data on the Western-Shebelinka area put under doubt the declared prognosis resources of hydrocarbons in this area; c) three DTAs were revealed by the FSPEF survey in the Shebelinka structure vicinities; d) massive hydrocarbon deposits are fixed by sounding diagrams on the Shebelinka field; e) the interval of intensive gas-and-oil content was fixed in a depth range of 5500–6600 m outside the Shebelinka structure; f ) the FSPEF-VERS technology can be used for an operative estimation of oil-and-gas content prospects of deep horizons (above 6000 m) of the sedimentary cover.